Policies and healthcare to support preconception planning and weight management: optimising long-term health for women and children - Jacqueline A Boyle; Jodie Dodd; Adrienne Gordon |; Brian W Jack; Helen Skouteris | (Sax Institute, 2022)
Objective: To explore opportunities to change increasing weight gain trajectories for women during their reproductive lives, focusing on optimising health before pregnancy. Type of program: Identifying optimal policies, health promotion and health services to support preconception health for women (with a focus on achieving a healthy weight). Methods: Narrative description of changing policies and approaches for improving preconception health. Results: Preconception preventive health priorities have been clearly determined globally and nationally. However, further rigorous research for effective interventions to facilitate healthy weight and other aspects of preconception health, alongside effective policies and strategies for implementing these interventions, remains potentially important. Barriers for women, their partners, families, communities and health professionals must be overcome and enablers fostered. The inclusion of preconception lifestyle health to tackle maternal and childhood obesity as a key priority of the World Health Organization as well as in the Australian National obesity strategy 2022-2032 are steps in the right direction. Lessons learnt: Improving health across the life course requires a whole of system, integrated and equitable approach to health promotion, healthcare and policy. This includes integrating education, work, community environments, and health professionals to engage girls and young women well before pregnancy, to optimise their health. National coordination to determine core indicators and systems to evaluate and monitor change has been shown to help internationally and can be applied in Australia.